Effective Complaint Handling for Strata Residential Property Managers - Yasmin Mohd Adnan; Zarita Ahmad Baharum; Abdul Ghani Sarip (2026)
As Malaysia's cities grow taller, more people are living in strata properties such as apartments and condominiums. Yet managing these shared communities remains challenging, especially when handling resident complaints effectively and fairly.This book explores how complaint management in Malaysia's strata housing can be improved. Based on data analysis, interviews, case studies, and international comparisons, it develops a practical, research-based Complaint Handling Framework for property managers, Joint Management Bodies (JMBs), and Management Corporations (MCs).Readers will gain:• A clear overview of strata living and Malaysia's regulatory framework.• Insights into common types of complaints, supported by a Klang Valley case study.• Clarification of the roles of developers, JMBs, and MCs under existing laws and regulations.• An overview of current management practices and technology tools used in the industry.• Key findings from surveys, site visits, and focus group discussions highlighting real operational gaps.• Lessons from international best practices, including examples from Singapore and Hong Kong.• Practical tools such as step-by-step complaint processes, models, and guideline templates.With the help of diagrams, summaries, and clear comparisons, this book gives practitioners and policymakers both an overall understanding and practical guide for change. It provides a clear and forward-looking framework to help Malaysia develop strata communities that are efficient, transparent, and truly liveable—supported by responsible and accountable management.